2006
DOI: 10.1590/s1516-84842006000400006
|View full text |Cite
|
Sign up to set email alerts
|

Perspectivas para a leucemia mielóide aguda na infância após a observação de um grupo de pacientes tratados convencionalmente

Abstract: O tratamento atual das leucemias mielóides agudas (LMA) obedece principalmente aos seguintes critérios: precisa caracterização clínica e biológica, adequada e agressiva quimioterapia, intensa terapia de suporte e possível indicação precoce de transplante de medula óssea. Neste artigo, envolvendo crianças tratadas entre 1986 e 1996, são apresentados os resultados passíveis de obtenção com tratamento quimioterápico convencional e discutidas as bases de implantação de um programa terapêutico moderno e de maior ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
2
1
0
1
Order By: Relevance
“…Analysis on the distribution of the FAB subtypes revealed predominance of AML- M4 followed by subtype AML-M1 in children. This result is similar to that found in research performed in São Paulo, 33 while a higher frequency of subtypes M2 and M3 was reported in Minas Gerais. 34 In contrast, work by the Berlin-Frankfurt-Münster (BFM) group in Germany showed higher frequency of subtypes M4 and M5.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Analysis on the distribution of the FAB subtypes revealed predominance of AML- M4 followed by subtype AML-M1 in children. This result is similar to that found in research performed in São Paulo, 33 while a higher frequency of subtypes M2 and M3 was reported in Minas Gerais. 34 In contrast, work by the Berlin-Frankfurt-Münster (BFM) group in Germany showed higher frequency of subtypes M4 and M5.…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to that found in research performed in São Paulo, 33 while a higher frequency of subtypes M2 and M3…”
supporting
confidence: 92%
“…Pesquisas de sobrevida populacional mostram probabilidades de sobrevida inferiores a 30%, salvo alguns subtipos, como a leucemia promielocítica aguda (LPA ou LMA-M3) e a LMA CBF (core binding factor) positivas [14][15][16][17] . Estudos brasileiros demonstraram sobrevida hospitalar ruim para LMA 1,2,8,18 , com sobrevida similar à descrita nos trabalhos internacionais 4,12,19,20 . Callera et al 9 , em São Paulo, observaram sobrevida hospitalar de 5 anos em 11,7% dos casos de LMA; Bittencourt et al 21 , no Rio Grande do Sul, relataram uma sobrevida hospitalar de 56 meses em 37% dos casos; e Souto et al 22 , no Rio de Janeiro, em uma série de casos no período de 2000 a 2008, relataram uma sobrevida hospitalar de 5 anos em 26% dos casos.…”
Section: Introductionunclassified
“…Given the enormous increase in our understanding of the underlying biology of AML, and the development of many new targeted drugs, it should be possible to achieve highquality cure in nearly all children and adolescents with AML within the next few decades [3,4].…”
mentioning
confidence: 99%